A Dose‐Tailored Anti‐Plasma Cell Regimen Lowers the Mortality of Late‐Stage Cardiac Amyloidosis - Yun Ti; Huaitao Yu; Ying Wang; Mei Ni; Tongtao Liu; Luqun Wang; Cheng Zhang; Peili Bu; Yun Zhang (MedComm, 2025)
ABSTRACT A major obstacle to using current guideline‐recommended chemotherapy in patients with advanced light‐chain cardiac amyloidosis (LCCA) is their intolerance to standard drug dosages. The study aimed to assess the efficacy and safety of the dose‐tailored BD and DBD regimen proposed by our team for patients with LCCA at Mayo Stage III. A total of 119 patients who met the inclusion and exclusion criteria for cardiac amyloidosis were recruited and divided into three groups: group A, group B, and group C who received supportive therapy, dose‐tailored BD regimen, and dose‐tailored DBD regimen, respectively. Survival rate and time, hematologic and cardiac response, and adverse events were evaluated during a median follow‐up of 30.2 months. No significant differences in baseline characteristics were found among the three groups. Group B and C showed increased survival rates and time compared to group A. Group C showed improved hematologic and cardiac responses relative to group B. Additionally, group C showed fewer adverse events related to chemotherapy compared to group B. Both dose‐tailored BD and DBD regimens increased survival rates and time in advanced LCCA patients, with the dose‐tailored DBD regimen demonstrating superior efficacy and safety. Further randomized clinical trials are needed to confirm these preliminary findings.